Determinants of internet usage: Relevance of financial development in the case of emerging markets? - Tsaurai, Kunofiwa; Chimbo, Bester (Acta Universitatis Danubius. Œconomica, 2022)
This study investigated the determinants of internet usage in emerging markets using panel data ranging from 2000 to 2017. It also explored whether the complementarity between financial and human capital development is one of the determinants of internet adoption in emerging markets. The study noted that the lag of internet, financial development, the complementarity between financial and human capital development, access to electricity, economic growth and foreign direct investment had a significant positive impact on the adoption of internet in emerging markets. The influence of import of internet goods on the adoption of internet to a larger extent was found to be significantly negative in emerging markets. On the other hand, the impact of urbanization on the usage of internet in emerging markets was found to be mixed to a greater extent. The study therefore urges emerging markets to implement policies aimed at boosting financial development, access to electricity, foreign direct investment, economic growth in order to increase the adoption of internet. Future related research should focus on determining the threshold levels of explanatory variables before they have a significant influence on internet.